2018
DOI: 10.13164/re.2018.0882
|View full text |Cite
|
Sign up to set email alerts
|

Improved Design and Implementation of Automatic Flight Control System (AFCS) for a Fixed Wing Small UAV

Abstract: This paper presents an implementation of automatic flight control system (AFCS); analyzes and assures its performance during model in loop (MIL), software in loop (SIL), and processor in loop (PIL) stages. Based on both linear and analytic linear models with trimmed values of straight and leveling scenario, the proposed autopilot is applied to an Ultrastick-25e fixed wing unmanned aerial vehicle (UAV). The implementation of Ultrastick-25e AFCS is accomplished according to the resulted design parameters, and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
(26 reference statements)
0
3
0
1
Order By: Relevance
“…In our future work, the computing time and the consuming-resources of the algorithm will be considered. Additionally, from recent research works [22,34,35] it can be observed that how controlling a UAV-based on phone sensors remains a problem. The control strategy based on the proposed algorithm will be investigated in future work.…”
Section: Discussionmentioning
confidence: 99%
“…In our future work, the computing time and the consuming-resources of the algorithm will be considered. Additionally, from recent research works [22,34,35] it can be observed that how controlling a UAV-based on phone sensors remains a problem. The control strategy based on the proposed algorithm will be investigated in future work.…”
Section: Discussionmentioning
confidence: 99%
“…In expansion, it is not possible to calculate nonlinear complex components logically contained within the streamlined strengths. For this reason, stochastic estimation strategies are utilized [3][4][5][6][7][8][9][10].…”
Section: F Fi Ig Gu Ur Re E 1 12mentioning
confidence: 99%
“…Управление полетом беспилотных летательных аппаратов различных типов (три-, квадрокоптеров) рассматривалось во многих работах 1 [1-4, 5, 6] как без учета внешних периодических нагрузок, так и с учетом, моделируемые силой сопротивления движению [7][8][9]. Выявлены зависимости отклонения реальной позиции аппарата от заданной при изменении значений коэффициентов регулятора и времени переходного процесса.…”
Section: Introductionunclassified